A framework for testing pathways from prenatal stress-responsive hormones to cardiovascular disease risk - Deer, LillyBelle K.; Su, Chen; Thwaites, Natalie A.; Davis, Elysia Poggi; Doom, Jenalee R. (Frontiers in Endocrinology, 2023)
Cardiovascular disease (CVD) is a leading cause of death globally, with the prevalence projected to keep rising. Risk factors for adult CVD emerge at least as early as the prenatal period. Alterations in stress-responsive hormones in the prenatal period are hypothesized to contribute to CVD in adulthood, but little is known about relations between prenatal stress-responsive hormones and early precursors of CVD, such as cardiometabolic risk and health behaviors. The current review presents a theoretical model of the relation between prenatal stress-responsive hormones and adult CVD through cardiometabolic risk markers (e.g., rapid catch-up growth, high BMI/adiposity, high blood pressure, and altered blood glucose, lipids, and metabolic hormones) and health behaviors (e.g., substance use, poor sleep, poor diet and eating behaviors, and low physical activity levels). Emerging evidence in human and non-human animal literatures suggest that altered stress-responsive hormones during gestation predict higher cardiometabolic risk and poorer health behaviors in offspring. This review additionally highlights limitations of the current literature (e.g., lack of racial/ethnic diversity, lack of examination of sex differences), and discusses future directions for this promising area of research.